Frequency and Antimicrobial Sensitivity Pattern Of Extended Spectrum β-Lactamases Producing E. Coli And Klebsiella Pneumoniae Isolated In A Tertiary Care Hospital - B. Sasirekha, R. Manasa, P. Ramya and R. Sneha (Al Ameen Medical College, 2010)
Infections due to extended spectrum β-lactamases (ESBL) producing Escherichia coli and Klebsiella pneumoniae have become an important clinical problem. Local knowledge of antimicrobial susceptibilities of these organisms is important for implementation of effective hospital anti-infective policies. The present study was undertaken to determine the prevalence of ESBLs along with their antimicrobial sensitivity pattern in Escherichia coli and klebsiella pneumoniae isolates at a tertiary care hospital in Bangalore. A total of 243 clinical isolates comprising E. coli (n=157) and K. pneumoniae (n=86) were recovered from various clinical samples over a period of six months from June to November 2008. Antibiogram profile of these isolates was determined by Kirby-Bauer's disc diffusion method. All the isolates were screened for ESBL production as recommended by the Clinical Laboratory Standard Institute (CLSI). The present findings revealed a high occurrence of multidrug resistance ESBL producing E. coli (61.1%) and K. pneumoniae (40.6%). Imipenem was highly active against ESBL producing isolates. Results indicate that routine ESBL detection should be made imperative and empirical use of third generation cephaolsporins must be discouraged.